Screening of Extracellular Enzymes on Serratia marcescens strain MBC1 - Meishy Handerlin Putri; Kusuma Handayani; Wawan A Setiawan; Berliana Damayanti; Cindy Lukyta Ratih; Achmad Arifiyanto (Universitas Negeri Surabaya, 2021)
Hydrolase enzymes are a class of enzymes used to break down the organic substrates into simpler molecules. Hydrolase enzymes play a role in biocontrol, industry, and public health. One of the hydrolase enzyme producers is bacteria. Serratia marcescens strain MBC1 is a collection in the Microbiology Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung which enzymatic activities havent been known yet. This research aimed to determine the enzymatic activity of S. marcesescens strain MBC1 that can be used as a candidate for biocontrol agents, biosurfactant producers, industry, or in the health sector. The screening was carried out using a qualitative method plate assay using selective solid media for each test, with three replications for each test. The data obtained were analyzed statistically using analysis non-parametric kruskall-wallis test. The lipolytic activity of the S. marcescens strain MBC1 showed high efficacy with an enzymatic index of 5.52 and amylase, cellulases, protease, mannanase, and chitinase with enzymatic indexes, respectively, 4.17, 1.50, 0.69, 0.35, and 0.27. This enzyme activity of this isolate can be used as a candidate for biological control agents,biosurfactant producers, industry, or the health sector.